The Tuskegee airmen : an illustrated history, 1939-1949 - Caver, Joseph (NewSouth Books, 2011)
Many doucmentaries, museums exhibits, books, and movies have now treated what became known as the "Tuskegee Experiment" involving black pilots who gained fame during World War II as the Tuskegee Airmen. Most of these works have focused on the training of America's first black fighter pilots and their subsequent accomplishments during combat. This publication goes further, using captioned photographs to trace the airmen through the stages of training, deployment, and combat actions in North Africa, Italy, and German, in an attractive coffee-table-book format. Included for the first time are depictions of the critical support roles of doctors, nurses, mechanics, navigators, weathermen, parachute riggers, and other personnel, all of whom contributed to help complete the establishment of the 477th Composite Group. The authors have told, in pictures and words, the full story of the Tuskegee Airmen and the environments in which they lived, worked, played, fought, and sometimes died.